Fiqh Perempuan Keindonesiaan - Lahaji Lahaji; Sulaiman Ibrahim (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2019)
Abstract:Women have more value than men. Women are bestowed with their feminine status that distinguishes them from men. The distinctive characteristics of women, who can get pregnant, give birth, and breastfeed, love, fortitude, and patience in educating children are the advantages of women. This article discusses women's fiqh in several concepts of meaning. First, women's fiqh is amaliyah laws in implementing Shari'a, for example the issue of marriage guardianship for women who want to carry out marriage. Second, women's fiqh is the arguments about the law regarding, for example, the proposition of women's leadership. From these two meanings, it was formulated that women's fiqh is an understanding of the law and the arguments relating to women in carrying out activities. Because women's fiqh is related to sharia law and thenaqli and aqli arguments, essentially women's fiqh in the sense of understanding the existence of women is the result of ijtihad called fiqh ijtihādiy. Therefore, it is not surprising that in understanding a legal object, the results of understanding (fiqh) produced by a mujtahid sometimes conflict with or differ from understanding (fiqh) obtained by other mujtahids.Keywords: Fiqh-Women-Indonesia.